2002
DOI: 10.1093/mutage/17.2.119
|View full text |Cite
|
Sign up to set email alerts
|

The CYP17 MspA1 polymorphism and breast cancer risk: a meta-analysis

Abstract: Inter-individual differences in susceptibility to breast cancer are partially mediated through the levels of endogenous and exogenous steroid hormones. The CYP17 gene encodes P450c17alpha, an enzyme that is involved in the metabolism of steroid hormones. Increased endogenous steroid hormone levels have been associated with a MspA1 polymorphism in the 5'-promoter region of the CYP17 gene. The CYP17 MspA1 polymorphism has been postulated as being associated with the risk of developing breast cancer. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 26 publications
5
39
1
Order By: Relevance
“…Of these two enzymes, CYP17 T to C polymorphic variant is implicated in osteoporotic predisposition. Most studies, however, could not establish a relationship between CYP17 TC polymorphism and circulating estrogen-androgen levels (Berstein et al, 2002;Feigelson et al, 2002;Kado et al, 2002;Ye and Parry, 2002;Somner et al, 2004). We also did not observe a statistically significant association between CYP17 TC polymorphism and sex steroid levels; however, there was a tendency of higher testosterone levels in osteoporotic patients compared to controls in the CYP17 TC genotype.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…Of these two enzymes, CYP17 T to C polymorphic variant is implicated in osteoporotic predisposition. Most studies, however, could not establish a relationship between CYP17 TC polymorphism and circulating estrogen-androgen levels (Berstein et al, 2002;Feigelson et al, 2002;Kado et al, 2002;Ye and Parry, 2002;Somner et al, 2004). We also did not observe a statistically significant association between CYP17 TC polymorphism and sex steroid levels; however, there was a tendency of higher testosterone levels in osteoporotic patients compared to controls in the CYP17 TC genotype.…”
Section: Discussioncontrasting
confidence: 82%
“…The CYP17 CC genotype was also found to show a very low frequency, probably because it is more pronounced in osteoporotic phenotypes as suggested by Somner et al (2004). CYP17 polymorphism could also play significant roles in testosterone synthesis, which functions in bone physiology, and therefore, it is possible that CYP17 is a strong candidate that functions in bone metabolism even though this gene has gender-specific effects on steroid metabolism (Zmuda et al, 2001;Ye and Parry, 2002;Sharp et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, this hypothesis could not be verified experimentally in vitro by Kristensen et al 8 Although the rs743572 SNP has been postulated for an association with the risk of developing breast cancer, a metaanalysis of 15 case-control studies did not find any overall association. 9 The result of our study showed that the C allele is associated with an increased risk of breast cancer in premenopausal women (OR 5 1.65, 95% CI 1.03-2.64). Recently, Chakraborty et al 10 also found the T to C polymorphism in the CYP17 gene was associated with an early onset breast cancer risk.…”
Section: Discussionmentioning
confidence: 54%
“…18,19 So far, a few studies suggested that the A2 allele might increase the risk of breast cancer, while other studies suggested no such association. 20,21 On the other hand, in prostate cancer, the relation between the CYP17 polymorphism and prostate cancer risk has been conflicting. Although a few groups including ours reported that the A1 allele of CYP17 increased the risk of prostate cancer, other studies reported a negative association or converse results.…”
Section: Discussionmentioning
confidence: 99%